PENGARUH KOMPETENSI TENAGA KERJA TERHADAP KUALITAS PRODUK INDUSTRI KECIL KONVEKSI DI KELURAHAN SELAMET KOTA JAMBI - Astuti, Weni Widia; Sembiring, Benar (Universitas Batanghari Jambi, 2021)
AbstractThis study aims to determine (1) to determine the quality of the product in the small convection industry in Selamat Subdistrict, Jambi City, (2) To determine the competence of workers in the convection industry in Selamat, Jambi City, (3) To determine the effect of labor competence on product quality in convection in Selamat Village, Jambi City. This research design uses descriptive quantitative research methods. With date collection techniques through observation, interviews, and questionnaires. Where the population in this study were 30 employees and a sample of 30 employees. The research instrument test technique used in this study is the validity and reliability test, while the classical assumption test used descriptive analysis test, normality test, homogeneity test, linearity test and simple regression test. While the hypothesis test in this study is a partial test (t test). The results of this study state that (1) the competence of the workforce is included in the good category with an average TCR value of 81.41%. (2) Product quality is included in the good category with an average TCR value of 84.49%. (3) The competence of the workforce affects the quality of the product which can be seen from tcount > ttable of 3.313 > 1.679. Then H0 is accepted, H1 is rejected. Thus, the competence possessed by a workforce, especially skills, will be seen from how a worker carries out his work. Meanwhile, the quality of the product can be seen from the reliability possessed by a product because it will increase the attractiveness of consumers towards the products they buy. Then the competence possessed by a worker will affect the quality of the product that will be produced. Especially skills and reliability because with the presence of these two indicators, the value will increase the added value, as well as the trust of consumers in the company's products.Keywords: Competency of Personnel, Product Quality